Performance and satisfaction in the occupations of multiprofessional residents before and during the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: to describe the performance and satisfaction of multiprofessional residents in their occupations before and during the COVID-19 pandemic. Material and Methods: descriptive, cross-sectional, quantitative study, with a sample defined by convenience, involving residents belonging to the Programs linked to the Multiprofessional Residency Commission (COREMU) who agreed to participate in the collection carried out from September to October 2020, using semi-structured, virtual questionnaire developed on the Google Forms platform. Results and discussion: The findings revealed that during the pandemic, residents showed a worsening of performance in all Activities of Daily Living, with the exception of the use of the toilet, intimate hygiene and functional mobility; drop in performance in all Instrumental Activities of Daily Living, except security and emergency maintenance in which they remained at the same level; as well as, decline in performance very good and good in all other occupations. Regarding the degree of satisfaction in the performance of occupations, the participants were more dissatisfied during the COVID-19 pandemic. Conclusion: the COVID- 19 pandemic favored negative impacts on the performance of most occupations, including the work and routine of residents, reflecting on the adaptation of a new structure of occupational life.